Sosialisasi Pembuatan Makanan dan Minuman Halal Toyyib Berbasis Bahan Pangan Alami di Kelurahan Merjosari, Lowokwaru, Malang - Tias Pramesti Griana; Azizatur Rahmah; Kholifah Holil; Ruri Siti Resmisari; Syarifah, Umaiyatus (Jurnal SOLMA, 2024)
Thoyyiban halal food is a fundamental requirement for the Muslim community in terms of fulfilling nutritional needs. The significance of halal and thoyyiban food lies not only in its role as a source of nutrition but also in its contribution to mental and spiritual well-being. Presently, there is a pressing issue within the community concerning the lack of attention during the selection of processing materials and procurement efforts. Natural ingredients serve as an alternative to address this issue. Consequently, community empowerment aims to socialize and provide training in the production of food based on halal and thoyyiban principles using natural ingredients in the Merjosari village, Malang. The type of community service carried out involves engaging the community not only as the object but also as the subject of the community service. The participants in this activity include the representatives of the Women's Welfare Movement (PKK) from sub-districts 3 and 4 of Merjosari, Lowokwaru, Malang. The community members are provided with socialization and training regarding the production of food based on halal and thoyyiban principles using natural ingredients. The results of this community service activity demonstrate a positive response from the participants. Data indicates a good level of understanding among the participants regarding the content and practices, amounting to 75%. This is evidenced by the participants' ability to select halal and thoyyiban ingredients and create flavor enhancer products using shrimp shells and health drinks